Development of a Local Food-Based MPASI Kitchen Integrated with the Golden1000 Application to Enhance Skills of Cadres and Mothers of Infants Aged 6-12 Months in Stunting Prevention - Sagita Imaniar, Melsa; Herdiani , Ida; Fitri , Sulidar; Reva Dewari, Ayu Dyah (Universitas Ahmad Dahlan, 2024)
Background : Bungursari Health Center led stunting cases in Tasikmalaya City in 2022 due to low exclusive breastfeeding rates and poor complementary feeding practices. This study addressed these issues through PMBA training, the Golden1000 app, and posyandu kitchen development. Contribution : PMBA training improved knowledge and skills in baby food preparation, promoted the Golden1000 app for 1000 HPK education, and fostered entrepreneurial posyandu kitchens. Metode : Training covered complementary food preparation, Golden1000 app use, and posyandu kitchen development. Results : The training and Golden1000 app usage improved knowledge and skills, leading to the formation of a posyandu kitchen. Conclusion : The program enhanced complementary food preparation skills and established a lasting posyandu kitchen initiative.